Global Optimality Conditions for Some Classes of Optimization Problems - Wu, Z. Y.; Rubinov, A. M. (Journal of optimization theory and applications, 2010)
We establish new necessary and sufficient optimality conditions for global optimization problems. In particular, we establish tractable optimality conditions for the problems of minimizing a weakly convex or concave function subject to standard constraints, such as box constraints, binary constraints, and simplex constraints. We also derive some new necessary and sufficient optimality conditions for quadratic optimization. Our main theoretical tool for establishing these optimality conditions is abstract convexity.